2008
DOI: 10.1073/pnas.0804408105
|View full text |Cite
|
Sign up to set email alerts
|

Flying in silence: Echolocating bats cease vocalizing to avoid sonar jamming

Abstract: Although it has been recognized that echolocating bats may experience jamming from the signals of conspecifics, research on this problem has focused exclusively on time-frequency adjustments in the emitted signals to minimize interference. Here, we report a surprising new strategy used by bats to avoid interference, namely silence. In a quantitative study of flight and vocal behavior of the big brown bat (Eptesicus fuscus), we discovered that the bat spends considerable time in silence when flying with conspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 40 publications
1
107
0
1
Order By: Relevance
“…Several jamming avoidance strategies used by echolocating bats have been reported, and all of these strategies involve modification in temporal/spectral features of self-generated signals (Bates et al, 2008;Chiu et al, 2009;Gillam et al, 2007;Obrist, 1995;Ulanovsky et al, 2004) or timing of signals (Chiu et al, 2008). However, no research so far has measured the sonar beam axes of two bats flying together and whether they adapt the directional sonar beam control to avoid signal interference.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several jamming avoidance strategies used by echolocating bats have been reported, and all of these strategies involve modification in temporal/spectral features of self-generated signals (Bates et al, 2008;Chiu et al, 2009;Gillam et al, 2007;Obrist, 1995;Ulanovsky et al, 2004) or timing of signals (Chiu et al, 2008). However, no research so far has measured the sonar beam axes of two bats flying together and whether they adapt the directional sonar beam control to avoid signal interference.…”
Section: Introductionmentioning
confidence: 99%
“…The flight behaviors of paired bats can be categorized into three types, converging, diverging and following flight, according to the inter-bat heading angle (the angle between each bat's velocity vectors), and the angle between the paired bats' separation vector and velocity vector (Table1). Detailed definitions of these flight behaviors were published in Chiu et al (Chiu et al, 2008). Following flight refers to the flight behavior when one bat was behind the other bat and both flew in a similar direction (i.e.…”
Section: Flight Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…AdZADH2 appears to support nitric oxide (NO) mediated HR cell death; NO production leads to the production of H 2 O 2 (instead of ROS), which in turn results in HR‐mediated PCD 54. Several lines of evidence have shown that the early nitric oxide (NO) burst in host plant cells after pathogen attack functions as a major defense response associated with resistance in plant pathogen interaction 55. NO is an interesting molecule that is used by microorganisms in pathogenesis and host cells to activate the immune system to counter the pathogen challenge 56, 57.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for the difference between acoustic and video detections is that some bats may have stopped calling while still approaching trees illuminated with UV. Insectivorous bats sometimes stop echolocating during flight in complex acoustic environments (Chiu et al 2008), and we speculate that they might also echolocate less frequently or even cease to echolocate when approaching visually unfamiliar objects (e.g. wind turbines; Cryan et al 2014).…”
Section: Discussionmentioning
confidence: 99%